2019
DOI: 10.1186/s12974-018-1393-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel neurotherapeutic for multiple sclerosis, ischemic injury, methamphetamine addiction, and traumatic brain injury

Abstract: Neurovascular, autoimmune, and traumatic injuries of the central nervous system (CNS) all have in common an initial acute inflammatory response mediated by influx across the blood-brain barrier of activated mononuclear cells followed by chronic and often progressive disability. Although some anti-inflammatory therapies can reduce cellular infiltration into the initial lesions, there are essentially no effective treatments for the progressive phase. We here review the successful treatment of animal models for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 89 publications
0
28
1
Order By: Relevance
“…As a potent proinflammatory cytokine, MIF is abundantly expressed in the pathological CNS of mammals and associated with clinical worsening of multiple sclerosis (MS), Alzheimer's disease (AD), and traumatic spinal cord ( 10 , 30 , 45 , 46 ). Astrocytes, together with microglia, are certainly the primary target cells of MIF and the active players that contribute to the inflammatory pathology ( 10 , 47 ). In the present study, gAS have been shown to be insensitive to the proinflammatory stimuli of gMIF, suggesting a unique inflammation-suppressive function of the immature adult astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…As a potent proinflammatory cytokine, MIF is abundantly expressed in the pathological CNS of mammals and associated with clinical worsening of multiple sclerosis (MS), Alzheimer's disease (AD), and traumatic spinal cord ( 10 , 30 , 45 , 46 ). Astrocytes, together with microglia, are certainly the primary target cells of MIF and the active players that contribute to the inflammatory pathology ( 10 , 47 ). In the present study, gAS have been shown to be insensitive to the proinflammatory stimuli of gMIF, suggesting a unique inflammation-suppressive function of the immature adult astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Partial major histocompatibility complex (MHC) Class II constructs can limit early immune response, therefore, sequestering ischemic-induced inflammation. [ 11 12 ] MHC Class II constructs are a viable stroke treatment because of their neuroantigen-specific modulation of T-cells as well as CD74 signaling. [ 11 12 15 ]…”
Section: Expanding Immune Responsementioning
confidence: 99%
“…[ 11 12 ] MHC Class II constructs are a viable stroke treatment because of their neuroantigen-specific modulation of T-cells as well as CD74 signaling. [ 11 12 15 ]…”
Section: Expanding Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the simpler DRhQ construct was designed, retaining just the conserved-in-human DRα1 domain (without the polymorphic HLA-DRβ1 domain) linked to the MOG-35-55 peptide extension, with the added benefit that it can be administered to all recipients without need for tissue type matching. This has enabled use of the DRα1-MOG-35-55 construct to reverse ongoing neuroinflammation and disease signs in animal models of multiple sclerosis, stroke, methamphetamine disorders and traumatic brain injury [8]. These and other studies ( [9][10][11] & unpublished data) revealed down-regulation of multiple proinflammatory components driven by both innate and adaptive immune responses that also contribute to the SARS-CoV-2 cytokine storm, including complement receptor C5aR1, platelet activation, IL-1β, IL-2, IL-6, TNF-α, CCR2 (receptor for CCL2) and CXCR2.…”
mentioning
confidence: 99%